To solve the system of equations given:
- \( y = -x + 2 \)
- \( 3x + 3y = 6 \)
First, we can rearrange the second equation to see if it matches the form of the first equation.
Start with the second equation:
\( 3x + 3y = 6 \)
Divide everything by 3:
\( x + y = 2 \)
Now, we can express \( y \) in terms of \( x \):
\( y = -x + 2 \)
This equation is identical to the first equation. Therefore, both equations represent the same line.
Since both equations describe the same line, there are infinitely many solutions (any point on the line is a solution to both equations).
Thus, the best description of the solution is:
There are infinitely many solutions.